Standardization of the Modeling System for Choosing the Reengineering Form to Change Business Processes at Critical Energy Infrastructure Enterprises: Challenges for Human Capital Security - Ostapchuk, Olha; Brych, Lesia; Lapychak, Nazariy; Prots, Roman; Kryshtanovych, Svitlana (Journal of Ecohumanism, 2024)
The topic of standardizing the modeling system for choosing the reengineering form to change business processes at critical energy infrastructure enterprises presents a complex interplay between technological advancements, process optimization, and the safeguarding of human capital. This discussion spans over several facets of organizational management, highlighting both the opportunities and challenges inherent in such transformative endeavors. The purpose of the article is to model the choice of the reengineering form to change business processes at critical energy infrastructure enterprises. The object of the study is a critical energy infrastructure enterprise. The methodology of the study involves the use of the IDEF0 method. As a result of the modeling, a model for choosing the reengineering form to change business processes at critical energy infrastructure enterprises is presented.